AB1400-HPR Muscle quality index in obese subjects with hip osteoarthritis. (12th June 2018) - Jerez, D.A; Machado, R.; Cerda, E.
Abstract : Background: Obese older adults with hip osteoarthritis suffer a progressive loss of neuromuscular function affecting their activities of daily living. Objectives: The objective of this study is to determine the behaviour of the muscular quality index in obese subjects with osteoarthritis and to compare the manifestations of strength and anthropometric variables with control subjects. Methods: Thirty-two subjects (4 men and 28 women, 66.2±5.2 years of age, 159.2±7.5 cm, 71.5±11.7 kg) were evaluated. 14 subjects suffered osteoarthritis. Muscle circumference, limb length, body mass and sit and stand test were evaluated, in addition to the maximal voluntary isometric contraction in hip flexion and extension movements. Results: The osteoarthritis group presented obesity (p=0.037). The muscle quality index of the osteoarthritis group correlated with the weight (p=0.776**), with maximum peak strength in flexion (p=0.552*) and average maximal strength (p=0.574*). In the control group the muscle quality index correlated with: weight (p=0.689**), muscle circumference (p=0.571*), maximum peak strength in extension (p=0.534*), average peak strength in extension (p=0, 523*), average maximal strength in extension (p=0.509*) and maximum impulse in extension (p=0.508*). Conclusions: The muscle quality index is a useful tool to measure muscle quality in the healthy population, but is not clear enough for obese subjects with osteoarthritis, so it is necessary to perform future studies to determine their behaviour. References: [1] Fragala MS, Kenny AM, Kuchel GA. Muscle quality in aging: a multi-dimensional approach to muscle functioning with applications for treatment. Sports medicine (Auckland, NZ). 2015;45(5):641–58. Epub 2015/02/07. doi: 10.1007/s40279–015–0305-z. PubMed PMID: 25655372. [2] Fragala MS, Fukuda DH, Stout JR, Townsend JR, Emerson NS, Boone CH, et al. Muscle quality index improves with resistance exercise training in older adults. Experimental gerontology. 2014;53:1–6. Epub 2014/02/11. doi: 10.1016/j.exger.2014.01.027. PubMed PMID: 24508922. [3] Barbat-Artigas S, Rolland Y, Zamboni M, Aubertin-Leheudre M. How to assess functional status: a new muscle quality index. The journal of nutrition, health & aging. 2012;16(1):67–77. Epub 2012/01/13. PubMed PMID: 22238004. [4] Takai Y, Ohta M, Akagi R, Kanehisa H, Kawakami Y, Fukunaga T. Sit-to-stand test to evaluate knee extensor muscle size and strength in the elderly: a novel approach. J Physiol Anthropol. 2009;28(3):123–8. PubMed PMID: 19483373. [5] van Lummel RC, Walgaard S, Maier AB, Ainsworth E, Beek PJ, van Dieën JH. The Instrumented Sit-to-Stand Test (iSTS) Has Greater Clinical Relevance than the Manually Recorded Sit-to-Stand Test in Older Adults. PLoS ONE. 2016;11(7):e0157968. doi: 10.1371/journal.pone.0157968. PubMed PMID: PMC4938439. Disclosure of Interest: None declared